1989
DOI: 10.1071/eg989245a
|View full text |Cite
|
Sign up to set email alerts
|

Porosity from seismic data, a geostatistical approach

Abstract: A geostatistical modelling technique called cokriging is used to describe the lateral variations of porosity, f, in a synthetic and a real reservoir. Using this method, an error-qualified porosity model is estimated for each of the two reservoirs from sparse well porosity measurements and seismically derived velocities. The method capitalizes on the high spatial density of the seismic measurements and on their correlation with f. Compared with conventional reservoir models derived solely from sparse well contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 0 publications
0
31
0
1
Order By: Relevance
“…In this framework, an optimal estimate of the mineralization grades, and thus the available resources, is likely achieved by integrating these different types of complementary data. The importance of integrating "hard" and "soft" spatial data has long been recognized in the petroleum industry, where reservoir properties such as permeability and porosity need to be inferred from a limited number of drill-holes (Doyen, 1988;Journel and Alabert, 1990;Le Ravalec-Dupin et al, 2001;Xu et al, 1992). Integrated modeling has also been used in the mining industry in ore reserve estimation (David, 1988;Journel and Huijbregts, 1978).…”
Section: Introductionmentioning
confidence: 97%
“…In this framework, an optimal estimate of the mineralization grades, and thus the available resources, is likely achieved by integrating these different types of complementary data. The importance of integrating "hard" and "soft" spatial data has long been recognized in the petroleum industry, where reservoir properties such as permeability and porosity need to be inferred from a limited number of drill-holes (Doyen, 1988;Journel and Alabert, 1990;Le Ravalec-Dupin et al, 2001;Xu et al, 1992). Integrated modeling has also been used in the mining industry in ore reserve estimation (David, 1988;Journel and Huijbregts, 1978).…”
Section: Introductionmentioning
confidence: 97%
“…. Acoustic data can be directly integrated as trends in simulation processes from cokriging [7] or preprocessed in terms of facies proportions [6]. In this last case, they are used to generate facies realizations from the sequential indicator simulation [12], the truncated Gaussian or Pluri-Gaussian methods [3] for instance.…”
Section: Description Of the History-matching Workflowmentioning
confidence: 99%
“…In CK, the secondary variable is not required at all nodes of the estimation grid. Doyen (1988) showed that the porosity of an oil-bearing sand of Alberta, Canada, predicted from CK is 20% more accurate, in a mean square sense, than that predicted from the standard singlevariate regression based on the well-log porosity and acoustic impedance (the product of density and velocity).…”
Section: Introductionmentioning
confidence: 98%